Instagram activities, engagement and enrollment intention in Indonesia: A case in the third largest island in the world - Juhaidi, Ahmad; Fuady, Mohammad Noor; Ramadan, Willy; Ma’ruf, Hidayat (Nurture, 2024)
Purpose: This study investigates the influence of diverse Instagram activities (entertainment, interaction, trendiness, advertisement and customization) on engagement levels and enrollment intention. Additionally, it aims to determine the impact of engagement on enrollment intention by exploring the mediating role of engagement in the relationship between social media activities and enrollment intention. Design/Methodology/Approach: The research involved 627 followers of the Antasari State Islamic University Banjarmasin Indonesia Instagram account. This study uses path analysis to better understand the impact of Instagram activities on enrollment intention and multiple linear regression to evaluate the influence of Instagram activities on enrollment intention with an emphasis on engagement as a mediating element in this relationship. Findings: The study found that Ig activity affects followers’ engagement from all backgrounds. Entertainment and interaction elements have an impact on high school students’ tendency to engage with followers. Furthermore, engagement affects enrollment intention. Advertisement affects enrollment intention with engagement as a mediator. Conclusion: This study validates previous research on Instagram (Ig) marketing’s impact on engagement in education. It underscores the greater complexity of Ig marketing in education than in business where enrollment decisions involve intricate considerations resulting in a generally lower influence of social media marketing on enrollment outcomes. Research Limitations: This study only focused on the Ig account of one university and was limited to Islamic higher education. Practical Implications: Higher education marketing administrators recommended combining social media marketing variables with other factors influencing university choice. Contribution to the Literature: This study finding has a conceptual contribution to higher education especially in social media marketing.